Kegiatan Pengabdian Masyarakat: Edukasi Kesehatan oleh Perawat untuk Meningkatkan Perilaku Hidup Sehat Masyarakat - Nurambiya, Nurambiya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Community service activities are essential efforts to improve public health quality. Nurses play a central role in providing health education to promote awareness and healthy living behaviors. This activity aimed to enhance community knowledge and behavior regarding health through education and simple practical demonstrations. The implementation method included material preparation, interactive health counseling, discussions, and pre–post knowledge evaluations. The results showed an increase in knowledge among 85% of participants, particularly in personal hygiene, healthy eating patterns, and physical activity. The community also demonstrated high enthusiasm in adopting healthy lifestyle practices in daily life. This program proves that health education conducted by nurses is effective in increasing community health awareness.